(untitled) (Altre Modernità, 2012)
A specialist text is rich in technical terms and is complex from the morphological and syntactical point of view. A foreign student, and perhaps an Italian-speaking one too, does not have a fund of knowledge or sufficient independence and control of linguistic and inferential processes necessary for comprehension. To help foreign students in their studies, they often tend to simplify specialist texts in Italian schools by intervening, as far as possible, in the language in which specialist knowledge is expressed. Thus, texts are prepared in which the vocabulary, morphology and syntax have been made easier and the contents reduced. Simplified texts used to make understanding specialist contents easier are often “a translation of a translation” and do not constitute a real model of a written text. They become mere service tools for understanding and for this reason the inevitable loss of information in some simplifications is even more delicate.